ERROR ANALYSIS OF THE STUDENTS’ TEST RESULT ON USING PERSONAL PRONOUNS - Suryani Suryani; Hidayatullah Hidayatullah (Jurnal Dedikasi Pendidikan, 2017)
The objectives of this research were to know the percentage of students’ error in using Personal Pronouns and to know what kind of Personal Pronouns error that is often made by the students. A case study which used a descriptive analysis was uttilized in this study. The sample of this research was students at grade X MIPA-1 of SMAN 1 Mesjid Raya. To get the data, the students were given 25 multiple choice questions about Personal Pronouns. Then, the students test paper were analyzed based on types of Personal Pronoun errors. The result of the analysis showed that the percentage error of Personal Pronouns were: Possesive Pronoun 70 (73,68%), Reflexive Pronoun 64 (67,36%), Possesive Adjective 63 (66,31%), Object Pronoun 59 (62,10%) and the least made errors are Subject Pronoun consisted of 40 errors (42,10%). Based on all of the findings above, it was found that the most errors which were made by students at the first grade of SMAN 1 Mesjid Raya, Aceh Besar; is in using Possesive Pronoun. These findings suggest that the students need to be given much attention and support by their teachers in understanding different types of personal pronouns in English.